Design of Autonomous Quadcopter Using Orientation Sensor with Variations in Load Fulcrum Point - Aisuwarya, Ratna; Marta Yonas, Fitra; Yendri, Dodon (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 10, No. 2 August 2019DO - 10.24843/LKJITI.2019.v10.i02.p03, 2019)
In designing the quadcopter, the main focus is stability and balance. Th us, in the more specific implementation, for example for aerial photography, a quadcopter can also be used as a load carrier. To be able to balance the quadcopter equipped with an orientation sensor on the controller, the orientation sensor includes a gyroscope sensor, accelerometer, and magnetometer. For this reason, it is necessary to have an autonomous stabilizer mechanism that can make the quadcopter stay in a stable and balanced condition even with the additional load. Furthermore, in this research, we will discuss how to determine the PID set points for quadcopter balance that can be tested on loads with different fulcrums. The test is limited to the condition of the quadcopter being hovered for pitch and roll angles. Based on the testing results , it can be concluded that t here is a stability response in the Quadcopter . I t can be seen from the RMS value obtained that it is by the steady-state tolerance of 2% -5% of the setpoint. Then, the Quadcopter can carry the maximum load with different fulcrums; 950g for fulcrum in the middle of the quadcopter, 580g for the l oad is placed 6 cm from the middle of the quadcopter, and 310g  if the load is placed on one motor .